2012
DOI: 10.1016/j.amjcard.2012.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Long-Term Outcome After Percutaneous Coronary Intervention Versus Coronary Artery Bypass Grafting in Patients With Unprotected Left Main Coronary Artery Disease (from the CREDO-Kyoto PCI/CABG Registry Cohort-2)

Abstract: The long-term outcome of percutaneous coronary intervention (PCI) compared to coronary artery bypass grafting (CABG) for unprotected left main coronary artery disease (ULMCAD) remains to be investigated. We identified 1,005 patients with ULMCAD of 15,939 patients with first coronary revascularization enrolled in the CREDO-Kyoto PCI/CABG Registry Cohort-2. Cumulative 3-year incidence of a composite of death/myocardial infarction (MI)/stroke was significantly higher in the PCI group than in the CABG group (22.7%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 17 publications
3
16
0
Order By: Relevance
“…6,7 The relevant ethics committees in all 26 participating centers (Supplementary data A) approved the research protocol. Because of retrospective enrollment, written informed consents from the patients were waived; however, we excluded those patients who refused participation in the study when contacted for follow-up.…”
Section: Methodsmentioning
confidence: 99%
“…6,7 The relevant ethics committees in all 26 participating centers (Supplementary data A) approved the research protocol. Because of retrospective enrollment, written informed consents from the patients were waived; however, we excluded those patients who refused participation in the study when contacted for follow-up.…”
Section: Methodsmentioning
confidence: 99%
“…5-7,13, 16 Therefore, in ULMCAD patients with relatively less anatomical complexity, represented by a low or intermediate SYNTAX score, PCI using DES is a reasonable alternative to CABG in real-world clinical practice. On the other hand, CABG still remains the preferable treatment for ULMCAD patients with high anatomical complexity (ie, high SYNTAX score or complex multivessel disease), because the clinical outcome after CABG is not affected by anatomical complexity.…”
Section: Discussionmentioning
confidence: 99%
“…12- 15 We previously reported 3-year outcome in patients with ULMCAD from the Coronary REvascularization Demonstrating Outcome Study in Kyoto (CREDO-Kyoto) PCI/CABG registry cohort-2, demonstrating that (1) 3-year clinical outcome of PCI was comparable with that of CABG in terms of serious cardiovascular events in patients with ULMCAD and (2) the risk for serious cardiovascular events was not significantly different between PCI and CABG in patients with low or intermediate SYNTAX score, but was markedly higher after PCI as compared with CABG in patients with high SYNTAX score. 16 In the current report, we extended the follow-up to evaluate longer-term (≥5 years) outcome of PCI compared with CABG in patients with ULMCAD in real-world clinical practice.…”
Section: Definitions and Endpointsmentioning
confidence: 99%
“…The most powerful data confirming the ability of the SxScore to predict differential clinical outcomes of patients with uLMCA disease undergoing percutaneous or surgical revascularization according to its different tertiles, come from the SYNTAX trial itself . An analysis by the CREDO/Kyoto PCI/CABG Registry Cohort‐2 provided confirmatory evidence to these results . Furthermore, Capodanno et al showed that patients with uLMCA disease and SxScore > 34 derive a mortality benefit from surgical revascularization compared with a PCI strategy.…”
Section: Discussionmentioning
confidence: 98%